A Case Report: Rare Communication of Ansa Cervicalis - Mohsen Noorozian; Mohammad Bayat; Reza Mastery Farahani; Mohammad-Amin Abdollahifar; Hadi Azimi; Ali Noori-Zadeh; Azam Asemi Rad; Somayeh Fallah Nejhad; Maryam Salimi; Hojjat-Allah Abbaszadeh (Negah Institute for Scientific Communication, 2015)
During the past few years, researchers and practitioners have developed novel techniques, using ansa cervicalis to innervate muscles of the larynx paralyzed due to surgical procedures carried out in the chest and neck areas. During routine dissection of a middle-age male cadaver, an unusual course of the superior root of the ansa cervicalis was observed. In this case, the superior root of the ansa cervicalis fused with the vagus and ran within the carotid sheath, and then joined the inferior root forming the ansa cervicalis in the anterior wall of the carotid sheath. The study of this case will add to our current knowledge of ansa cervicalis and thus aid prevention of injury to the nerve during various surgical procedures.